Analyzing the senior consumers’ attitude toward advertising: traditional and new media - Gonçalves, Diogo Francisco Maio (2015)
Senior consumers have received limited attention from researchers and practitioners. Therefore, advertising managers become reliant on limited research and standing stereotypes to set their strategies. At the same time, more and more people start spending more time in later adulthood than in any other traditional marketing life stage. These senior consumers are healthier and wealthier than their ancestors were at their age. This reality is not exclusive to western countries, in fact in a few years this aging of the population will take over many of the current stars of economic growth: Places like China and South Korea also face serious population aging. This dissertation focuses on the perceptions of seniors about ads presented on the new media. Two studies were conducted to explore the way senior consumers perceive ads presented on TV (traditional media) and YouTube (new media), the first study was a experiment conducted in a senior university which gathered 107 observations, and the second a focus group interview. Firstly, it was discovered that seniors seem to be more efficient at avoiding ads on TV than on YouTube; secondly it was found that due to the different ways and purposes seniors use TV and YouTube for, ads presented on YouTube may cause more irritation than on TV; thirdly it was learnt that skepticism toward advertising messages may be higher for ads presented on YouTube than on TV; finally, it was also discovered that for seniors, attitude toward advertising does not seem to vary across different media.